Implementation of Rehabilitation Policy for Drug Addicts by the National Narcotics Agency Jakarta - Mumtaz, Emka Farah; Kusworo, Kusworo; Taher, Bahrudin; Suprajogo, Tjahjo (International Journal of Law Policy and Governance, 2025)
This paper aims to analyse the implementation of the drug addict rehabilitation policy conducted by the National Narcotics Board of DKI Jakarta Province (BNNP DKI Jakarta). The study focuses on evaluating the effectiveness of rehabilitation programmes, identifying supporting and inhibiting factors, and formulating recommendations for strengthening drug policy in Indonesia. A descriptive qualitative approach was employed, using Grindle’s policy implementation model as the analytical framework. Data were collected through in-depth interviews, direct observations, and document analysis. Informants were selected through purposive and snowball sampling, consisting of policy makers, policy implementers, and rehabilitation beneficiaries. The data were analysed through reduction, presentation, and conclusion drawing in line with the Miles and Huberman model, with validity ensured through triangulation of sources, methods, and time. The findings reveal that although the rehabilitation policy is supported by strong legal frameworks such as Law No. 35/2009 and SEMA No. 4/2010, its implementation remains constrained by limited resources, weak inter-agency coordination, and persistent social stigma against drug users. Rehabilitation programmes have largely focused on medical recovery, while social reintegration and post-rehabilitation support remain insufficient, leading to high relapse rates. Nevertheless, family and community support, cross-sectoral collaboration, and institutional commitment serve as important enabling factors in programme success. This study contributes to the literature by addressing the provincial-level implementation gap in Indonesia’s drug rehabilitation policy. It introduces the Neo-Grindleian on Drugs model, which integrates six strategic pillars: adaptive regulation, institutional synergy, resource optimisation, community engagement, evidence-based evaluation, and programme sustainability. The model provides a more inclusive and technology-oriented approach to rehabilitation, expected to enhance the effectiveness and humanistic orientation of public policy in addressing drug abuse.